Homogenous amniotic membrane as a biological dressing for oral mucositis in rats: Histomorphometric analysis - Vilela-Goulart, Maria das Gracas; Santos Teixeira, Raquel Teodoro; Ranyel, Daniela Coelho [UNESP]; Niccoli-Filho, Walter; Gomes, Monica Fernandes [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Objective: oral mucositis is a frequent and significant side effect of chemotherapy and/or radiation therapy. The purpose of this study was to evaluate the effects of the homogenous amniotic membrane (HAM) as a biological dressing for oral mucositis induced by 5-fluorouracil (5-FU) in the labial fornix region of inferior incisors in rats.Methods: Sixty rats were divided into three groups: control (50% acetic acid), 5-FU (50% acetic acid and 5-fluorouracil-induced oral mucositis) and 5-FU + HAM (50% acetic acid and 5fluorouracil-induced oral mucositis, and treated with HAM). Histological analyses were done 3, 7, 14 and 21 days after applying the acetic acid.Results: HAM showed not only no signs of rejection as well as an excellent tissue adherence to the ulcerated surface. Histomorphometric analysis indicated a lower quantity of inflammatory cells in the 5-FU + HAM group in all periods when compared to the other groups and there was a statistically significant difference in the 3- and 7-day periods (P < 0.001).Conclusions: The results of this study suggest that HAM was biocompatible with great adhesive power to the ulcerated surface, accelerated the healing process and exhibited anti-inflammatory activity. Further studies should be done to investigate the potential benefits of this material in clinical trials. HAM could lead to improved results as a biological dressing in treatment and management of oral mucositis in patients submitted to chemotherapy and/or radiation therapy. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Homogenous amniotic membrane; Biological dressing; Oral mucositis; Healing process; 5-Fluorouracil